(untitled) (مجلة إحالات, 2026)
We are trying، through this research paper، to highlight the theoretical and conceptual aspects related to Islamic literature and to explain the reasons for its emergence among Arab writers. It is "the expression that arises from the fulfillment of the self with Islamic feelings" (in history، idea، and approach). This is what we find in the works of his brother، Muhammad Qutb: "Islamic literature is the aesthetic expression of the universe، humanity، and life through the Islamic conception of existence" (Islamic Art Approach). The views of Eastern literature critics and scholars do not differ from the views of their Maghreb counterparts، as described by the martyred writer Ahmed Reda Houhou، who defined it as "...a living language that addresses the souls of others، it is the sincere thought about our feelings and the depths of our souls from the images of life، and thus it becomes a mirror of the nation، otherwise it is the nonsense of idols of the nation. This is the literature we desire، free and rich with stories، novels، criticism، and poetry". What interests us in this study is to discuss the concept of intertextuality، its types، mechanisms، and functions، as well as the concept of Islamic literature and its characteristics, some of Najib AlKilani’s modern Islamic literary works.